PENGARUH PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR CAMAT KIKIM SELATAN KABUPATEN LAHAT - Hestin, Hestin (Universitas Muhammadiyah Palembang, 2021)
Purpose – to determine the effect of curry development and organizational commitment on employee job satisfaction at the Kikim Selatan sub-district office, Lahat RegencyDesign/methodology – This research is a descriptive and comparative study using a quantitative approach which aims to determine the influence between two or more variables. This study analyzes the influence of the independent variables on the dependent variable.Findings - The results of the discussion obtained the value of Y = 0.897 + 0.455 + 0.555. A constant value of 0.897 means that if the independent variables are ignored, the value of the Job Satisfaction variable (Y) is 0.897. The value of the Career Development variable (X1) is 0.455 which means that if the Career Development variable (X1) is increased by 0.455 it will increase Job Satisfaction (Y) by 0.455. The value of the Organizational Commitment variable (X2) is 0.555 which means that if the Organizational Commitment variable (X2) is increased by 0.555 it will increase Job Satisfaction (Y) by 0.555.The results of the analysis by testing jointly explain the calculated F value of 121.961, with a significant level of 0.000, then the Sig value is 0.000, which means Sig 0.000 <0.05 then Ho is rejected and Ha is accepted. This means that the Career Development (X1) and Organizational Commitment (X2) variables simultaneously have a significant effect on Job Satisfaction (Y).